MACEDONIAN NATIONAL INNOVATION SYSTEM – MAIN CHALLENGES - Radmil Polenakovik (Economic Review, 2014)
It is generally accepted that the National Innovation Systems (NIS) are one of the most comprehensive systemic approaches that give insight into innovative and economic performance of a country. This insight is essential for policymakers to develop legislatives for enhancing the innovative performance and success of today’s knowledge based economies. The development of the NIS is a complex, path-dependant process due to the differences in the development of the main sectors involved: the academia and the industry. Macedonian later emergence of the NIS is explained by the fact that after 1990, with the collapse of the Socialist Federal Republic of Yugoslavia (SFRY) there were significant losses in the Yugoslav, East and Central European markets. This process was accompanied by disintegration of many large industrial complexes, leading to a large number of bankruptcies and lay - offs. The existing strong governmental support for the scientific and research projects in the Federation was disrupted and disabled by these rapid changes, which was also reflected in the breakdown of direct links between academia and industry. The following two decades were transitional, and this period of recovery was terminated with the adoption of several strategic documents such as: industrial policy; program for science -research work and technological development; innovation strategy; and strategy for intellectual property. Finally, in 2013 the Law on Innovation Activity, which includes establishment of Innovation Fund, was adopted.This paper aims to retrospect the main activities for developing innovation infrastructure and enhancing innovation capacities. Moreover, it offers critical assessment of the improvements and the main challenges faced. The presented overview is designed to assist policymakers in further monitoring, evaluation and improvements, and to provide researchers with a solid base for the additional in - depth analysis of the impact of the implemented and proposed measures.